ANALISIS UJI TIDAK MERUSAK PADA SAMBUNGAN LAS LAMBUNG FRAME 103 BAGIAN KAMAR MESIN KAPAL PATROLI 73 DENGAN METODE RADIOGRAPHY TEST - Sulaiman, Sulaiman; Utomo, Budi; Ardi Wijana, I Putu Agung (Gema Teknologi, 2020)
Non-Destructive Test is a supporting tool that is highly relied upon by the activities of controlling and ensuring the quality of a welding. Radiography test is one of the non-destructive tests that uses gamma rays that can penetrate almost all metals so that it can be used to reveal defects or discrepancies behind metal walls or within the material itself. The purpose of this paper is to know, plan a non-destructive testing activity with radiography test which includes the understanding along with the equipment needed during the testing process, what devices contribute to the testing process, as well as knowing the advantages and disadvantages of the test radiography. The method used in This writing is by experiment with welding connection frame 103 Patrol Ship 73 engine rooms. Radiography Test results found no welding defects on the inside of the welding as deep as a plate thickness, so that otherwise passed the checking received by BKI. Good preparation and consideration are needed before conducting this test.